2017
DOI: 10.1002/jhrm.21284
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve employee health and well‐being within health care organizations: A systematic review

Abstract: In response to an increasing body of evidence on the importance of employee health and well-being (HWB) within health care, there has been a shift in focus from both policymakers and individual organizations toward improving health care employee HWB. However, there is something of a paucity of evidence regarding the impact and value of specific HWB interventions within a health care setting. The aim of this article was to systematically review the literature on this topic utilizing the EMBASE, Global Health, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Staff HWB should be considered a resource worth investing in because the greatest asset to the healthcare system is said to be the people who deliver it [ 8 ]. In this financially difficult time for the NHS, this may require scrutiny of what makes an effective HWB intervention, reallocation of resources and changes to the ways or patterns of working [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staff HWB should be considered a resource worth investing in because the greatest asset to the healthcare system is said to be the people who deliver it [ 8 ]. In this financially difficult time for the NHS, this may require scrutiny of what makes an effective HWB intervention, reallocation of resources and changes to the ways or patterns of working [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased risk of obesity that hospital employees face, we know little regarding intervention characteristics and their impact on obesity prevention among health care employees. To our knowledge, few reviews have thus far evaluated the effects of employee well-being interventions among health care professionals (Chan & Perry, 2012; Power, Kiezebrink, Allan, & Campbell, 2014; Williams et al, 2018). However, these reviews either excluded studies using quasi-experimental designs or did not focus on worksite obesity prevention strategies targeting all types of health care employees.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that healthcare workers have higher rates of suicide, burnout, minor mental disorders, hypertension, hyperlipidaemia, and asthma when compared to rates in other occupations, general workers, or the general population [6][7][8][9]. Data on healthcare workers in the United Kingdom show that sickness rates were four times higher than rates seen in other sectors [10].…”
Section: Introductionmentioning
confidence: 99%